Nesting patterns among Neotropical species assemblages: can reserves in urban areas be failing to protect anurans? - Lourenço-de-Moraes, Ricardo; Malagoli, Leo R. [UNESP]; Guerra, Vinicius; Ferreira, Rodrigo B.; Affonso, Igor De Paiva; Haddad, Célio F. B. [UNESP]; Sawaya, Ricardo J.; Bastos, Rogério P. (Springer Nature, 2018)
Nestedness among species assemblages implies that sites of lower species richness are subsets of richer sites in a regional species pool. This nestedness is a reflection of a non-random process of species loss as a consequence of factors that promote the disaggregation of assemblages. The impoverishment of assemblage diversity is more often observed in fragmented landscapes. This non-random process has important implications for conservation. We recorded 95 species of anurans across 22 protected areas, of which 11 sites were in an urban matrix and 11 were in a non-urban matrix. We found that sites in the urban matrix had lower richness and high values of nestedness with no spatial autocorrelation among geographic distances and species composition. Thus, species were non-randomly distributed across the landscape and a nested pattern was documented from non-urban matrix sites to urban matrix sites. The impoverishment of assemblages toward the urban matrix sites may suggest that protected areas in an urban matrix are less suitable for anuran conservation than those in a non-urban matrix sites. Both the ecological revitalization of protected areas in urban matrix and protection of non-urban forested sites are needed for the conservation of Neotropical anurans.
Keywords: Atlantic Forest; Biodiversity; Fragmentation; Hotspot; Metacommunities